2005
DOI: 10.1021/om050206e
|View full text |Cite
|
Sign up to set email alerts
|

The First Structurally Characterized Homoleptic Aryl-Manganese(III) Compound and the Corresponding Isoleptic and Isoelectronic Chromium(II) Derivative

Abstract: The homoleptic organochromium(II) compound [Mg(THF) 6 ][Cr II (C 6 F 5 ) 4 ] (1) was obtained as an extremely air-sensitive solid by reaction of [CrCl 2 (THF)] with C 6 F 5 MgBr. The arylation of MnBr 2 under similar conditions proceeded with oxidation of the metal center to give [Mg-(THF) 6 ][Mn III (C 6 F 5 ) 4 ] 2 (2). The crystal structures of 1 and 2 (X-ray diffraction) contain the anions [Cr(C 6 F 5 ) 4 ] 2and [Mn(C 6 F 5 ) 4 ] -, respectively, both with approximate square-planar (SP-4) geometry around t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 42 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…3) where the cation is formed by an octahedral magnesium surrounded by six molecules of THF whereas the anionic moiety consists of two zinc atoms bonded to two chlorine bridges and two terminal ones in a distorted tetrahedral geometry. Several examples of other mixed-metal compounds containing either one of these two ions, separately but never together, have been reported (23)(24)(25)(26). However, surprisingly a search of the Cambridge Crystallographic Database revealed that the 1∶2, Mg∶Zn stoichiometry found in compound 3 is extremely rare across the whole of mixed magnesium-zinc chemistry, with only three such compounds structurally characterized to date (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…3) where the cation is formed by an octahedral magnesium surrounded by six molecules of THF whereas the anionic moiety consists of two zinc atoms bonded to two chlorine bridges and two terminal ones in a distorted tetrahedral geometry. Several examples of other mixed-metal compounds containing either one of these two ions, separately but never together, have been reported (23)(24)(25)(26). However, surprisingly a search of the Cambridge Crystallographic Database revealed that the 1∶2, Mg∶Zn stoichiometry found in compound 3 is extremely rare across the whole of mixed magnesium-zinc chemistry, with only three such compounds structurally characterized to date (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…However, by reacting MnBr 2 with the Grignard reagent Mg(C 6 F 5 )Br, compound [Mg(thf) 6 ]-[Mn III (C 6 F 5 ) 4 ] 2 was obtained as a result of a combined arylation and oxidation process (Scheme 2). 31 In contrast with the behaviour observed for Mn, the reaction of FeCl…”
Section: Magnetic Propertiesmentioning
confidence: 80%
“…While the C 6 F 5 rings are almost perpendicular to the metal coordination plane in [Cr II (C 6 F 5 ) 4 ] 2− (Fig. 9), 31 the C 6 Cl 5 rings in [Cr II (C 6 Cl 5 ) 4 ] 2− adopt a helical arrangement around the normal to that plane (Fig. 10), 28 again introducing a source of chirality.…”
Section: Configuration Would Be Expected (See Below)mentioning
confidence: 99%
“…7 Similar Cr-C bond distances (average Cr-C = 215.8(6) pm) were also found in the homoleptic square-planar (SP-4) organochromium(II) derivative [Mg(thf) 6 ][Cr II (C 6 F 5 ) 4 ]•2thf, regardless of the different oxidation state of the metal centre. 12 It is reasonable to assume that the change in coordination number would compensate for the decrease in the Cr-C distance expected to occur on going from Cr II to Cr III . The C 6 F 5 groups in 2 and 3 adopt a heavily tilted disposition with respect to the equatorial plane (tilt angles: 44.0-55.8 • ), while in the aforementioned homoleptic Cr II derivative they were found to be roughly perpendicular to the coordination plane (tilt angles: 74.8-88.8 • ).…”
Section: Synthesis and Structural Characterisationmentioning
confidence: 99%